Brace performance with steel curved dampers and amplified deformation mechanisms. (15th November 2018) - Hsu, H.-L.; Halim, H.
Highlights: New A-Brace design that adopted steel curved damper with amplified deformation for performance improvement was proposed. Effective equation to evaluate the strength of the proposed A-Brace was presented and validated. Important experimental information on A-Brace performance was presented. Effective viscous damping was achieved in the proposed A-Brace design. Significant energy dissipation mechanism for seismic design was accomplished in the proposed method. Abstract: This study focused on the performance evaluation of new brace designs that adopted steel curved dampers with amplified-deformation mechanisms. A series of cyclic load tests on steel curved dampers and amplified-deformation braces with various damper dimensions, subjected to cyclic increasing displacement histories, were conducted. Expressions for amplified-deformation brace strength estimation were derived and proposed for engineering design references. Test results showed that significant viscous damping, approximately 25.8–36.65%, was achieved in the proposed brace, thus providing an effective mechanism to upgrade the dynamic characteristics of the structures. It was also found from the test results that the proposed braces sustained large deformation equivalent to 5% story drift without damper local buckling, exhibited stable hysteretic behavior throughout the complete load process and dissipated significant energy using amplified damper deformation, when steel curved dampers with plate depth/thickness ratios smaller than four were adopted. Simultaneous accomplishments in high strength, large deformation capability and significant energy dissipation validated the applicability of the proposed brace design to earthquake-resistant structural designs.